Experiments with Snails Add to Our Knowledge about the Role of aPKC Subfamily Kinases in Learning - Chesnokova, Ekaterina (Int J Mol Sci, 2019)
Protein kinase Mζ is considered important for memory formation and maintenance in different species, including invertebrates. PKMζ participates in multiple molecular pathways in neurons, regulating translation initiation rate, AMPA receptors turnover, synaptic scaffolding assembly, and other processes. Here, for the first time, we established the sequence of mRNA encoding PKMζ homolog in land snail Helix lucorum. We annotated important features of this mRNA: domains, putative capping sites, translation starts, and splicing sites. We discovered that this mRNA has at least two isoforms, and one of them lacks sequence encoding C1 domain. C1 deletion may be unique for snail because it has not been previously found in other species. We performed behavioral experiments with snails, measured expression levels of identified isoforms, and confirmed that their expression correlates with one type of learning.